Chromosomal Studies of Three Malayan Island Rats - Yong, Hoi Sen; Dhaliwal, S.S.; Teh, K.L. (Japan Mendel Society, 1972)
In recent years, there has been an ever-increasing accumulation of information pertaining to comparative mammalian cytogenetics (cf. Benirschke 1969). The chromosomes of rodents have also been reviewed (Nadler 1969). Of the Malayan rats (genus Rattus Fischer), the karyotypes of all 18 mainland species have been recently described (Yong 1968 and 1969). There are, however, no reports on the chromosomes of the Malayan island rats. The present paper deals with the karyotypes of three rats of Malaya. According to Chasen (1940) and Hill (1960), these island rats belonging to subgenus Rattus are forms of Rattus rattus. Medway (1969), however, considered "most populations of rats of this group on Malayan islands are probably representatives of R. tiomanicus rather than Rattus rattus...".